Physiology of perception of saline stress in ‘Common Sunki’ mandarin hybrids under saline hydroponic solution - Sá, Francisco Vanies da Silva; Brito, Marcos Eric Barbosa; Silva, Luderlândio de Andrade; Moreira, Romulo Carantino Lucena; Fernandes, Pedro Dantas; Figueiredo, Lizaiane Cardoso de (Comunicata Scientiae, 2015)
In order to study the physiology of perception of saline stress in ‘Common Sunki’ mandarin hybrids, an experiment was realized in a greenhouse at the CCTA - UFCG, Pombal, PB, Brazil,using using a randomized block design with a 2x4 factorial , with two levels of salinity (0.3 and 4.0 dS m-1) and four ‘Common Sunki’ mandarin hybrids (1 - TSKC x CTARG–019; 2 - TSKC x CTSW–028; 3 - TSKC x CTSW–033 and 4 - TSKC x CTSW-041), with three replications and four plants per plot. The plants were grown hydroponically and 90 days after sowing, a saline water solution was applied on rootstocks and evaluations of gas exchange and chlorophyll fluorescence were carried out 24 and 48 hours after saline stress. Changes on physiologic conditions were observed in the hybrids TSKC x CTSW - 028, TSKC x CTSW - 033 and TSKC x CTSW - 041 during the first 24 hours of saline stress. Fot the hybrid TSKC x CTARG – 019, changes were observed after 48 hours od salinity stress. According to salinity tolerance, the hybrids could be classified as follows: TSKC x CTARG - 019 > TSKC x CTSW - 028 = TSKC x CTSW – 041 > TSKC x CTSW - 033.